(untitled) (Applied Biological Research, 2025)
Field experiments were conducted to evaluate the effect of different bioformulations in combination with varying levels of inorganic fertilizers on plant nutrient (N, P and K) availability in soil and their uptake by garlic (Allium sativum L.) during the rabi seasons of 2022–2023 and 2023–2024. The experiments were carried out at the Medicinal and Aromatic Plant Research Station, Sri Konda Laxman Telangana State Horticultural University (SKLTGHU), Rajendranagar, Hyderabad, India. The study was laid out in a factorial randomized block design comprising ten treatments, including a control, with three replications. Results indicated significantly higher nitrogen (2.14%) and phosphorus (0.59%) contents in plants, along with greater nitrogen and phosphorus uptake (98.62 and 27.42 kg ha⁻¹, respectively), under the treatment receiving 50% N + 100% P + 50% K combined with Azotobacter @ 5 kg ha⁻¹, potassium-solubilizing bacteria @ 6 kg ha⁻¹, Trichoderma viride @ 10 mL L⁻¹ and sesame oil @ 0.5%, compared to other treatments. The highest available soil nitrogen, phosphorus and potassium (166.85, 38.31 and 137.22 kg ha⁻¹, respectively), along with maximum potassium content (1.85%) and uptake (82.99 kg ha⁻¹) in plants, were recorded under the treatment comprising 50% N + 50% P + 100% K supplemented with Azotobacter @ 5 kg ha⁻¹, phosphorus-solubilizing bacteria @ 5 kg ha⁻¹, Trichoderma viride @ 10 mL L⁻¹ and neem oil @ 0.5%. The findings highlight the importance of evaluating integrated combinations of inorganic fertilizers, bioagents and botanicals to improve nutrient availability, uptake, and overall physiological and nutritional performance of garlic. , , , , , pongamia oil, ,